ANALYSIS OF E-WALLET USING SATISFACTION THROUGH INTENTION TO CONTINUOUS USE: EMPIRICAL STUDY IN TANGERANG DISTRICT - Dihin Septyanto; Dewi Astutik; Rojuaniah Rojuaniah; Ikramina Larasati Hazrati Havidz; Diana Fajarwati (SEAN Institute, 2023)
This study aims to examine the variables that influence e-wallet user intentions in 2023 in making decisions to reuse digital payments, in this case Shopeepay. These variables are perceived convenience, perceived usefulness, subjective norms, attitudes, confirmations, habits, trust, and user satisfaction. Questionnaires were distributed to 191 respondents to collect data. This study selected respondents using a purposive sampling method. This study is a quantitative study using the Structural Equation Model (SEM) method with data processing and analysis using the SmartPLS device. Test the validity and reliability with factor analysis using SPSS. Some of the findings in this study are perceived convenience, perceived usefulness, subjective norms, attitudes, and confirmations that have an indirect significant effect on the intention to reuse e-wallets through user satisfaction. While the habit variable has no significant effect on reuse intention. Meanwhile, the moderating effect of trust has a significant effect on the intention to reuse e-wallet services. The coefficient of determination (R-Square) for perceived ease of use and perceived usefulness through the intervening attitude variable is 0.644 or 64.40%. While the variable subjective norm, attitude, and confirmation through the intervening user satisfaction variable is 0.689 or 68.90%, meaning that the opportunity for other variables to explain is 31.10%. Based on this, it can be concluded that habit is not necessarily a significant determining factor in the intention to continue use. Meanwhile, perceived usefulness, perceived ease of use, attitude, subjective norm, confirmation, user satisfaction, and trust factors can influence consumer intentions to use Shopeepay services so companies are expected to pay more attention to these matters to increase consumer intentions to reuse Shopeepay digital payment services.